(untitled) (Praxis Educativa, 2023)
The article presents the progress of a cartography of educational and pedagogical initiatives in Latin America that contribute to the construction of social justice in educational scenarios. The research that originates it developed diálogos de saberes with educators who build just emancipatory praxis and who are committed to building other educational realities in which decolonized, depatriarchalized and decapitalized individual and collective subjectivities are formed in their ways ofthinking and acting. The guiding thread ofthese reflections is the stubborn hope that another world and, therefore, another education is possible, by denaturalizing injustices, breaking structurally installed binarisms and inequalities and, from the subjective power, weaving in the micropolitical daily life of the classroom and the institutions, just praxis.